2012
DOI: 10.1002/adhm.201200069
|View full text |Cite
|
Sign up to set email alerts
|

Antibody‐Targeted Drug Delivery to Injured Arteries Using Layered Double Hydroxide Nanoparticles

Abstract: Targeted local delivery of a nanoparticle-based, antibody-targeted, and low molecular weight heparin (LMWH) delivery system successfully reduces restenosis and thrombus formation in an animal model. An antibody recognizing cross-linked fibrin (XLF) D-dimer is successfully conjugated to layered double hydroxide nanoparticles. Use of the anti-XLF-conjugated LMWH-carrying layered double hydroxide nanoparticles shows successful targeting of the nanoparticles (red) to the injured artery wall (green), resulting in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 25 publications
0
43
0
2
Order By: Relevance
“…118 In the case of LDH nanocarriers, recent progress in targeting moiety design has been seen in conjugating folic acid and antibody agents. 20,57,[119][120][121] Folic acid has a high affinity (K d E 100 pM) for folate receptors which are often overexpressed in various human cancers, such as ovary, lung, kidney, colon cancer, etc.…”
Section: Ldh@targeting Moietymentioning
confidence: 99%
“…118 In the case of LDH nanocarriers, recent progress in targeting moiety design has been seen in conjugating folic acid and antibody agents. 20,57,[119][120][121] Folic acid has a high affinity (K d E 100 pM) for folate receptors which are often overexpressed in various human cancers, such as ovary, lung, kidney, colon cancer, etc.…”
Section: Ldh@targeting Moietymentioning
confidence: 99%
“…We further showed that this antibody effectively targeted LDH nanoparticles to the site of arterial injury, and that the sustained release of LMWH from the nanoparticles inhibited neointimal formation and thrombus development in a rat model of arterial injury [97]. .…”
Section: Nanoparticle-mediated Targeted Delivery Of Anti-restentoic Dmentioning
confidence: 86%
“…Antibodies recognising fibrin have been conjugated to a number of potential therapies, to target the drugs to the site of fibrin formation, that is, the site of injury. Various antibody-drug therapies have been shown to reduce thrombosis, neointimal formation and vessel remodelling, as well as improving reendothelialization in the vessel [102,[104][105][106][107]131].…”
Section: Antibody-or Peptide-targeted Therapiesmentioning
confidence: 99%
“…Nanoparticles are 1-100 nm in size, with a large surface area, and often have magnetic and fluorescent properties [131,134,135,142] be better protected from degradation, making them available for longer periods and enhancing their therapeutic effects. This is a particular advantage for hydrophilic drugs, which are otherwise readily lost.…”
Section: The Use Of Nanoparticles In Targeted Drug/gene Deliverymentioning
confidence: 99%
See 1 more Smart Citation